Diorama : a novel - Bensimon, Carol, 1982- (MCD/Farrar, Straus and Giroux, 2026)
"Based on real events, the daughter of an assassin flees Brazil to outrun the aftermath of the murder and ensuing scandal that defined her young life"-- Provided by publisher.